Evaluasi Faktor Keberhasilan Sistem Informasi Transportasi Online Berbasis Mobile Dalam Perspektif Kepuasan Pelanggan - Verry Riyanto; Susy Rosyida; Ridwansyah Ridwansyah (LPPM Universitas Bina Sarana Informatika, 2019)
Abstract - One of the most important sectors in determining the success of the development process in developing countries is transportation. Existing transportation such as land, air and sea transportation. Of the three types of transportation, in Indonesia, the fastest development of island transportation. The rapid growth of transportation is evidenced by the increasing number of motorcycle transportation by 7.40% per year. This amount is supported by factors in the development and utilization of information technology that is increasingly growing in Indonesia. Behind that, it turns out there is support from the many companies developing technology to build transportation applications. As with online transportation that can provide land transportation facilities only by utilizing smartphone technology. The development of online transportation is one of the important factors in the use of transportation vehicles in Indonesia. Previous transportation has the facilities and infrastructure in the use of transportation is still minimal, namely the lack of providing services to the community so that people do not feel satisfied. Therefore, we conducted a study to evaluate the success factors of using land transportation from an online transportation application in the perspective of customer satisfaction using the AHP method that can overcome complex, unstructured problems such as expert thought, from the results obtained by the main factors that are very influential with the success of an application can be seen from the level of technological confidence of the application.Keywords: Success Factors, Customer Satisfaction.